Mapping sustainable practices and concepts in the transportation ecosystem for the EU-27 countries, based on LinkedIn company profiles - Tsironis, Georgios; Karagkouni, Aristi; Dimitriou, Dimitrios; Tsagarakis, Konstantinos P. (Frontiers in Sustainability, 2023)
Sustainability has been a topic of growing interest over the past years with many governments, organizations, and companies trying to achieve the Sustainable Development Goals. The major challenge of implementing more sustainable practices within the corporate environments is still in the foreground, probably even in higher demand, due to the intense environmental degradation and the strict deadlines related to the decarbonization and shift towards greener production systems. Indicatively, the European Commission suggests that transport currently accounts for a quarter of the European Union's (EU) greenhouse gas emissions and this figure continues to rise as demand grows. In this work, we investigate the tTransportation sector, distribution systems, and supply chain through the prism of sustainability by mining and analyzing open-access data on the LinkedIn social media platform, which is widely used for professional networking, especially, in the European market. Thus, we extract valuable insights into the current trends around sustainability within the transportation sector. More precisely, 1640 LinkedIn profiles registered as "companies" related to transportation have been data mined providing valuable outputsinsights regarding their sustainabilityoriented activities. Our datasetsample containsreferred to companies with a staff range of over 200 employees, aiming to gain insights from medium SMEs and large organizations/companies. A key Key findings of our analysis includerefers to the differentiation of application areas regarding sustainable conceptspractices and the rise of the percentage of sustainability-related companies with the company staff size combined with a rather strong connection between the United Kingdom's and USA's transportation sectors.